Impulsiveness and its impact on behavioural intention and use of mobile shopping apps: a mediation model. (8th May 2019) - Chopdar, Prasanta Kr.; Sivakumar, V.J.
The unified theory of acceptance and use of technology 2 (UTAUT2) is applied and extended to explore the adoption and use of mobile shopping apps in India. This study adds impulsiveness construct to the original model. The data gathered from 328 respondents were evaluated using the partial least square structural equation modelling (PLS-SEM) method. All construct (i.e., performance expectancy, effort expectancy, facilitating conditions, hedonic motivation, habit and impulsiveness), except for social influence and price value were found to significantly relate to behavioural intention to use mobile shopping applications. Behavioural intention, habit and impulsiveness were found to significantly influence use behaviour of mobile shopping apps, except for facilitating conditions. Moreover, significant mediating influences were reported in the study. The findings of the study provide valuable insights and suggestions for mobile marketers and developers of shopping apps to enable their increased adoption and use. Further, the mediating roles of performance expectancy, effort expectancy and habit have been explored in the model.